Yield gap analysis of major food crops in Pakistan: prospects for food security - Khan, Imran; Lei, Hongdou; Khan, Ahmad; Muhammad, Ihsan; Javeed, Tehseen; Khan, Asif; Huo, Xuexi (Environmental science and pollution research international, 2021)
The concept of yield gap analysis can be used to meet the growing demands for agricultural products. Sustainable development goals (e.g. SDG1 and SDG2) to end poverty and hunger require sustainable increases in agricultural production in developing countries, particularly in South Asia and Africa. The aim of this paper is to assess the spatial heterogeneity of the potential and actual yields of major food crops and to determine the yield gaps at the provincial and national levels in Pakistan. The regional test yields of the registered cultivars were used to determine the potential grain yields and total potential grain production levels in each province of Pakistan. The yield gaps were then calculated by comparing the potential and actual yields of the selected major food crops. With a substantial exploitation rate of 0.38 in total grain production, a significant potential gap was found at the national level. The results revealed that the national potential of total grain production is 100,933 Mg, and the actual national grain production from 2015 to 2016 was 38,227 Mg, with a production gap of 62,706 Mg. The results further revealed that the maize crop had the highest potential gap on a national basis, followed by wheat and rice. Meanwhile, on provincial basis, the total production gaps of Punjab, Sindh, Khyber Pakhtunkhwa and Balochistan are 43,776 Mg, 9649.3 Mg, 6772.1 Mg and 2510.7 Mg, respectively. Moreover, based on climate, temperature, rainfall and topography, the yield gaps varied from crop to crop and from province to province. To increase grain yields and close the yield gaps of the major crops, the farmland infrastructure should be strengthened and resource allocations should be optimized. The findings of this study can provide conclusive data for national grain production, protection and food security.